2018
DOI: 10.1016/j.bcp.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional interaction between GPR18 and cannabinoid CB2 G-protein-coupled receptors. Relevance in neurodegenerative diseases

Abstract: GPR18, still considered an orphan receptor, may respond to endocannabinoids, whose canonical receptors are CB and CB. GPR18 and CB receptors share a role in peripheral immune response regulation and are co-expressed in microglia, which are immunocompetent cells in the central nervous system (CNS). We aimed at identifying heteroreceptor complexes formed by GPR18 and CBR or CBR in resting and activated microglia. Receptor-receptor interaction was assessed using energy-transfer approaches, and receptor function b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 54 publications
1
47
0
Order By: Relevance
“…Due to its presence in microglia, CB2 may also be a promising target [174]. Interestingly, CB2 forms heterodimers with GPR18, which exhibit considerable interactions, thus GPR18 may be a promising target, although more research is needed [175]. Moreover, β-amyloid promotes MAGL overexpression.…”
Section: Neurodegenerationmentioning
confidence: 99%
“…Due to its presence in microglia, CB2 may also be a promising target [174]. Interestingly, CB2 forms heterodimers with GPR18, which exhibit considerable interactions, thus GPR18 may be a promising target, although more research is needed [175]. Moreover, β-amyloid promotes MAGL overexpression.…”
Section: Neurodegenerationmentioning
confidence: 99%
“…Among the studies previously mentioned, only one investigated the mechanisms underlying the effects of treatment with RvD2 in a model of depression. In particular, they showed that improvement in depressive-like behavior was observed in mice after intracranial RvD2 administration, which was independently mediated by GPR18, a G-protein-coupled receptor activated by cannabinoids (61) and RvD2, mTORC1, and MAP/ERK signaling (36).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Cells were grown in Dulbecco's modified Eagle's medium (DMEM) supplemented with 2 mM L-glutamine, 100 U/ml penicillin/streptomycin, and 5% (v/v) heat inactivated fetal bovine serum (FBS) (Invitrogen, Paisley, Scotland, United Kingdom). Cells were maintained in a humid atmosphere of 5% CO 2 at 37 • C. Cells were transiently transfected with the polyethylenimine (PEI, Sigma, St. Louis, MO, United States) method (38)(39)(40). Briefly, cells were incubated (4h) in a serum-starved medium with the corresponding cDNA and with PEI (5.47 mM in nitrogen residues) and 150 mM NaCl.…”
Section: Cell Culture and Transient Transfectionmentioning
confidence: 99%